Exploration of Chemopreventive Potential of Linalool in Targeting Lung Cancer Biomarkers - Singh, Jyoti; Meena, Abha (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Phytochemicals are used to treat lung cancer in contemporary and traditional medicine. The limitations of known chemotherapeutic drugs such as non-specificity, resistance, and toxicity restrict their use for lung cancer treatment. Therefore, the search for target-specific novel entities is required continuously. Objective: Linalool, a monoterpene alcohol that possesses antiviral, anti-inflammatory, and antibacterial properties, is present in sweet basil, laurel, jasmine, rosewood, and lavender. Previous reports revealed its anticancer potential against colon, breast, and liver cancer. In this study, linalool's efficacy in targeting biomarkers associated with different lung cancer stages has been investigated. Methods: The in silico molecular docking analysis was used to explore drug-receptor interaction, and further, linalools cytotoxicity potential was evaluated on lung adenocarcinoma cell line (A549). The toxicity profiling of linalool was done by ADMET analysis. Results: In the results, Linalool revealed an excellent binding affinity with the selected targets. It showed the highest interaction with BRAF with the binding energy of -5.6 kcal/mol. Furthermore, it successfully interacts within the binding pocket of BRAF, similar to its inhibitor (Sorafenib). In MTT analysis, linalool significantly reduces the percent viability IC30 474.94 ± 43.12, 379.33 ± 49.5, and 183.77 ± 66.7 μM in A549 cell lines for 24, 48, and 72 h, respectively. Conclusion: These results concluded that linalool possesses chemopreventive potential against lung cancer by interacting or modulating selected biomarkers associated with a lung cancer diagnosis, progression, and proliferation.
Keywords: kinase